Visual function in term infants with hypoxic-ischaemic insults: correlation with neurodevelopment at 2 years of age. Issue 2 (1st March 1999) - Mercuri, Eugenio; Haataja, Leena; Guzzetta, Andrea; Anker, Shirley; Cowan, Frances; Rutherford, Mary; Andrew, Rachel; Braddick, Oliver; Cioni, Giovanni; Dubowitz, Lilly; Atkinson, Janette
Abstract : AIMS: To determine if there is any association between the findings of visual assessment performed at the age of 5 months and neurodevelopmental outcome at the age of 2 years in children who have sustained hypoxic-ischaemic insults. METHODS: Twenty nine term infants with hypoxic–ischaemic encephalopathy and/or brain lesions on neonatal magnetic resonance imaging (MRI) were prospectively evaluated. At 5 months of age all the infants had their visual function assessed using the Atkinson Battery of Child Development for Examining Functional Vision, which includes the assessments of optokinetic nystagmus (OKN), acuity, visual fields, fixation shift and phase and orientation reversal visual evoked potentials. At 2 years of age the children had a structured neurological evaluation and a Griffiths developmental assessment. RESULTS: There was good correlation between the extent of the early detected visual impairment and both neuromotor and global development. Children with more than three out of five abnormal visual tests at 5 months of age tended to have abnormal neurological examination results and abnormal developmental quotients. Children with three or fewer abnormalities tended to have developmental quotients in the normal range; the level of their performance, however, was still related to the number of visual tests passed. CONCLUSIONS: Individual visual tests can provide important prognostic information. While abnormal OKN and acuity were always associated with abnormal outcome, normal results on visual evoked potentials and fixation shift tended to be associated with normal outcome.